Behavioral Analysis for Detecting Code Clones - Bayu Priyambadha; Siti Rochimah (Universitas Ahmad Dahlan, 2018)
The activities of copy and paste fragments of code from a source code into the other source code is often done by software developers because it's easier than generate code manually. This behavior leads to the increase of effort to maintain the code. One of the detection methods of semantic cloning is based on the behavior of the code. The code behavior detected by observing at an input, output and the effects of the method. Methods with the same value of input, output, and effect will indicate that semantically the same. However, the detection method based on the input, output, and effect could not be used in a void method or method without parameters, another side comprehensively detection is required. The challenge is how to detect which variable in a method that acts as input, output, and effect. Detection of the variable input, output, and effects in a void method done using Program Dependence Graph. The use of clone detection methods semantically based on behavior can increase the agreement value.